Influenza-associated excess respiratory mortality in China, 2010–15: a population-based study - Li, Li; Liu, Yunning; Wu, Peng; Peng, Zhibin; Wang, Xiling; Chen, Tao; Wong, Jessica Y T; Yang, Juan; Bond, Helen S; Wang, Lijun; Lau, Yiu Chung; Zheng, Jiandong; et al. (The Lancet. Public health, 2019)
The estimation of influenza-associated excess mortality in countries can help to improve estimates of the global mortality burden attributable to influenza virus infections. We did a study to estimate the influenza-associated excess respiratory mortality in mainland China for the 2010–11 through 2014–15 seasons. We obtained provincial weekly influenza surveillance data and population mortality data for 161 disease surveillance points in 31 provinces in mainland China from the Chinese Center for Disease Control and Prevention for the years 2005–15. Disease surveillance points with an annual average mortality rate of less than 0·4% between 2005 and 2015 or an annual mortality rate of less than 0·3% in any given years were excluded. We extracted data for respiratory deaths based on codes J00-J99 under the tenth edition of the International Classification of Diseases. Data on respiratory mortality and population were stratified by age group (age <60 years and ≥60 years) and aggregated by province. The overall annual population data of each province and national annual respiratory mortality data were compiled from the China Statistical Yearbook. Influenza surveillance data on weekly proportion of samples testing positive for influenza virus by type or subtype for 31 provinces were extracted from the National Sentinel Hospital-based Influenza Surveillance Network. We estimated influenza-associated excess respiratory mortality rates between the 2010–11 and 2014–15 seasons for 22 provinces with valid data in the country using linear regression models. Extrapolation of excess respiratory mortality rates was done using random-effect meta-regression models for nine provinces without valid data for a direct estimation of the rates. We fitted the linear regression model with the data from 22 of 31 provinces in mainland China, representing 83·0% of the total population. We estimated that an annual mean of 88 100 (95% CI 84 200–92 000) influenza-associated excess respiratory deaths occurred in China in the 5 years studied, corresponding to 8·2% (95% CI 7·9–8·6) of respiratory deaths. The mean excess respiratory mortality rates per 100 000 person-seasons for influenza A(H1N1)pdm09, A(H3N2), and B viruses were 1·6 (95% CI 1·5–1·7), 2·6 (2·4–2·8), and 2·3 (2·1–2·5), respectively. Estimated excess respiratory mortality rates per 100 000 person-seasons were 1·5 (95% CI 1·1–1·9) for individuals younger than 60 years and 38·5 (36·8–40·2) for individuals aged 60 years or older. Approximately 71 000 (95% CI 67 800–74 100) influenza-associated excess respiratory deaths occurred in individuals aged 60 years or older, corresponding to 80% of such deaths. Influenza was associated with substantial excess respiratory mortality in China between 2010–11 and 2014–15 seasons, especially in older adults aged at least 60 years. Continuous and high-quality surveillance data across China are needed to improve the estimation of the disease burden attributable to influenza and the best public health interventions are needed to curb this burden. National Science Fund for Distinguished Young Scholars, National Science and Technology Major Project of China, National Institute of Health Research, the Harvard Center for Communicable Disease Dynamics from the National Institute of General Medical Sciences, and the China-US Collaborative Program on Emerging and Re-emerging Infectious Disease.